2020
DOI: 10.3389/fncel.2020.00041
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of the Time Course of Acidification Decreases the Acid-Sensing Ion Channel 1a Current Amplitude and Modulates Action Potential Firing in Neurons

Abstract: Acid-sensing ion channels (ASICs) are H +-activated neuronal Na + channels. They are involved in fear behavior, learning, neurodegeneration after ischemic stroke and in pain sensation. ASIC activation has so far been studied only with fast pH changes, although the pH changes associated with many roles of ASICs are slow. It is currently not known whether slow pH changes can open ASICs at all. Here, we investigated to which extent slow pH changes can activate ASIC1a channels and induce action potential signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 49 publications
(71 reference statements)
4
52
0
Order By: Relevance
“…Experiments with ultrarapid perfusion systems have shown that ASICs activate with time constants of the order of 10 ms (Bassler et al, 2001, Sutherland et al, 2001, Alijevic et al, 2020). In the measuring chamber used in this study, the RT of solution change was ∼300ms ( Materials and Methods) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments with ultrarapid perfusion systems have shown that ASICs activate with time constants of the order of 10 ms (Bassler et al, 2001, Sutherland et al, 2001, Alijevic et al, 2020). In the measuring chamber used in this study, the RT of solution change was ∼300ms ( Materials and Methods) .…”
Section: Discussionmentioning
confidence: 99%
“…These kinetics are slower than the current and ΔF measured for ASIC activation by pH in many experiments. It is known from experiments with ultrarapid perfusion systems and excised patches that the intrinsic kinetics of ASIC activation are of the order of ∼10 ms (Bassler et al, 2001, Sutherland et al, 2001, Alijevic et al, 2020, Vaithia et al, 2019). Therefore, the ASIC activation kinetics are in most studies limited by the speed of the perfusion change.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations